Penerapan Strategi Inquiry dalam Pembelajaran Pendidikan Agama Islam - Arlina, Arlina; Ramadhan, M. Rayhan; Pohan, Nelliana; Mandasari, Dayanti; Nurhasanah, Nurhasanah (ANWARUL, 2023)
This study examines the application of the inquiry strategy in learning Islamic religious education. This type of qualitative research, the method of literature seen by the authors from various journals, theses and books. The results of the conclusions obtained regarding learning the application of inquiry strategies in learning Islamic religious education are very significant. because it can make students active in finding and understanding the material being studied through preparatory steps, stimulus, problem identification, collecting data, data processing, proof, drawing conclusions so that students can truly understand the material.